Alcohol in fatal crashes involving Mexican and Canadian drivers in the USA. Issue 5 (10th March 2011) - Baker, Susan P; Brady, Joanne E; Rebok, George W; Li, Guohua
Abstract : Objective: To determine the prevalence of alcohol involvement and impairment in fatal crashes in the USA involving Mexican and Canadian drivers. Methods: Drivers in fatal crashes in the USA were identified during 1998 to 2008 from the Fatality Analysis Reporting System, and the prevalence of alcohol involvement and impairment (defined as blood alcohol concentrations ≥0.01 g/dl and ≥0.08 g/dl, respectively) was compared among drivers licensed in Mexico (n=687), Canada (n=598), and the USA (n=561 908). Results: The prevalence of alcohol involvement was 27% for US drivers, 27% for Mexican drivers, and 11% for Canadian drivers. Alcohol impairment was found in 23% of US drivers, 23% of Mexican drivers, and 8% of Canadian drivers. With adjustment for driver demographic characteristics and survival status and for crash circumstances, the prevalence of alcohol involvement was significantly lower for Canadian drivers (adjusted prevalence ratio (PR) 0.63, 95% CI 0.49 to 0.80) than for US drivers, and was similar between Mexican and US drivers (adjusted PR 0.91, 95% CI 0.81 to 1.02). Conclusions: Alcohol involvement in fatal motor vehicle crashes in the USA is similarly prevalent in US and Mexican drivers, but is substantially less common in Canadian drivers.